Rapamycin Expands and Confers Resistance to Apoptosis of Human Inducible Regulatory T Cells (TRI). (May 2013) - Bergmann, C.; Wild, C.A.; Hoffmann, T.K.; Lang, S.; Whiteside, T.L.
The immunosuppressive drug Rapamycin (RAPA) has been shown to promote expansion of CD4 + IL-10 + natural human regulatory T cells (nTreg) in vitro and in vivo . RAPA effects on inducible Treg (Tri) are unknown, and this study explores in vitro responses of Tr1 to this drug. CD4 + CD25 neg T cells isolated from PBMC of normal donors were used to generate Tr1 cells. Expanded Tr1 cells were tested for surface markers, expression of survival proteins, resistance to apoptosis and the ability to suppress proliferation of autologous CD4 + CD25 neg responder T cells (RC) in functional assays. RAPA was found to promote the generation of human Tr1 cells from autologous CD4 + CD2S neg precursors in peripheral blood. Tr1 cells + RAPA mediated higher suppression (p<0.01) of RC proliferation than Tr1 cells cultured without RAPA. Tr1 cells + RAPA also expressed higher levels of FasL and granzyme B (p<0.002), produced more IL-10 and TGF-βl and were more resistant to activation-induced cell death (p<0.02). RAPA up-regulated expression of the Bcl-2 family anti-apoptotic proteins in Tri. In addition, stimulation of Tr1 by LPS + RAPA resulted in increased proliferation and resistance to apoptosis. RAPA favors in vitro generation of inducible human Treg (Tr1) from CD4 + CD25 neg precursor cells and significantly enhances their survival and suppressor functions.